Hadith #5142 - Sunan Abi Dawud - Abu al-Tufayl, 'Amir bin Wathla; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amarah bin Thuban عمارة بن ثوبان حجازي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
While we were with the Messenger of Allah! (ﷺ) a man of Banu Salmah came to Him and said: Messenger of Allah is there any kindness left that I can do to my parents after their death? He replied: Yes, you can invoke blessings on them, forgiveness for them, carry out their final instructions after their death, join ties of relationship which are dependent on them, and honour their friends.
Grade: Hasan